Understanding women's uptake and adherence in Option B+ for prevention of mother-to-child HIV transmission in Papua, Indonesia: A qualitative study. - Christina Lumbantoruan; Michelle Kermode; Aloisius Giyai; Agnes Ang; Margaret Kelaher (PLoS ONE)
Background Despite a more proactive approach to reducing new HIV infections in infants through lifelong treatment (Option B+ policy) for infected pregnant women, prevention of mother-to-child transmission of HIV (PMTCT) has not been fully effective in Papua, Indonesia. Mother-to-child transmission (MTCT) is the second greatest risk factor for HIV infection in the community, and an elimination target of <1% MTCT has not yet been achieved. The purpose of this study was to improve understanding of the implementation of Option B+ for PMTCT in Papua through investigation of facilitators and barriers to women's uptake and adherence to antiretroviral therapy (ART) in the program. This information is vital for improving program outcomes and success of program scale up in similar settings in Papua. Methods In-depth interviews were conducted with 20 women and 20 PMTCT health workers at two main referral hospitals for PMTCT in Papua. Development of interview guides was informed by the socio-ecological framework. Qualitative data were managed with NVivo11 software and themes were analysed using template analysis. Factors influencing women's uptake and adherence in Option B+ for PMTCT were identified through final analysis of key themes. Results Factors that motivated PMTCT uptake and adherence were good quality post-test HIV counselling, belief in the efficacy of antiretroviral (ARV) attained through personal or peer experiences, and a partner who did not prevent women from seeking PMTCT care. Key barriers for PMTCT participation included doubts about ARV efficacy, particularly for asymptomatic women, unsupportive partners who actively prevented women from seeking treatment, and women's concerns about community stigma and discrimination. Conclusions Results suggest that PMTCT program success is determined by facilitators and barriers from across the spectrum of the socio-ecological model. While roll out of Option B+ as current national policy for pregnant women in Papua has improved detection and enrolment of HIV-positive women, health facilities need to address various existing and potential issues to ensure long-term adherence of women beyond the current PMTCT program, including during pregnancy, childbirth and breastfeeding.